Monismo e pluralismo nas concepções realistas do conceito de espécie biológica: análise e crítica - Pereira, Karine Rossi (2017)
This work discusses and analyses realist conceptions of the concept of biological species. There are two broad realist approaches to this concept, viz. the monist approach and the pluralistic approach. Monist conceptions sustain that the species category must be conceptualized through only one species concept, providing just one criterion of delimitation of taxa. On the other side, pluralistic conceptions claim that different concepts correspond to the species category, so that there would be distinct criteria for the delimitation of taxa. Some of the most influential monist conceptions are presented under the titles “biological species concept”, “evolutionary species concept”, “ecological species concept’ and “Henning’s species concept”. Because they employ only one criterion of taxa delimitation, monist conceptions do not satisfy the theoretical requirements for the conceptualization of the diversity of natural organisms. Under this light, pluralistic concepts of species are possible alternatives to monist concepts and their respective problems. This work highlights two pluralistic approaches among those prominent in the current literature: Philip Kitcher’s ontological pluralism approach, also called pluralistic realism, and Richard A. Richards’ approach, called conceptual division of labor. These approaches will be analyzed and discussed along with the monistic concepts presented here, in order to adjudicate their adequacy to the solution of the species concept problem.